Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Let's solve the equation step-by-step to find the value of [tex]\( x \)[/tex] from the given options.
The given equation is:
[tex]\[ -10x + 1 + 7x = 37 \][/tex]
### Step 1: Combine Like Terms
First, we need to simplify the left-hand side of the equation by combining like terms.
[tex]\[ -10x + 7x + 1 = 37 \][/tex]
Combine the [tex]\( x \)[/tex] terms:
[tex]\[ -3x + 1 = 37 \][/tex]
### Step 2: Isolate the Variable Term
Next, we want to isolate the variable term [tex]\(-3x\)[/tex]. To do this, subtract 1 from both sides of the equation:
[tex]\[ -3x + 1 - 1 = 37 - 1 \][/tex]
Simplifying this, we get:
[tex]\[ -3x = 36 \][/tex]
### Step 3: Solve for [tex]\( x \)[/tex]
To find [tex]\( x \)[/tex], divide both sides of the equation by [tex]\(-3\)[/tex]:
[tex]\[ x = \frac{36}{-3} \][/tex]
Simplifying this, we obtain:
[tex]\[ x = -12 \][/tex]
So, the solution to the equation is [tex]\(-12\)[/tex].
### Step 4: Verify with Given Options
We are given the options:
- [tex]\( x = -15 \)[/tex]
- [tex]\( x = -12 \)[/tex]
- [tex]\( x = 12 \)[/tex]
- [tex]\( x = 15 \)[/tex]
From our calculated result, the correct value of [tex]\( x \)[/tex] is [tex]\(-12\)[/tex].
Thus, the solution to the equation [tex]\(-10x + 1 + 7x = 37\)[/tex] is:
[tex]\[ \boxed{-12} \][/tex]
The given equation is:
[tex]\[ -10x + 1 + 7x = 37 \][/tex]
### Step 1: Combine Like Terms
First, we need to simplify the left-hand side of the equation by combining like terms.
[tex]\[ -10x + 7x + 1 = 37 \][/tex]
Combine the [tex]\( x \)[/tex] terms:
[tex]\[ -3x + 1 = 37 \][/tex]
### Step 2: Isolate the Variable Term
Next, we want to isolate the variable term [tex]\(-3x\)[/tex]. To do this, subtract 1 from both sides of the equation:
[tex]\[ -3x + 1 - 1 = 37 - 1 \][/tex]
Simplifying this, we get:
[tex]\[ -3x = 36 \][/tex]
### Step 3: Solve for [tex]\( x \)[/tex]
To find [tex]\( x \)[/tex], divide both sides of the equation by [tex]\(-3\)[/tex]:
[tex]\[ x = \frac{36}{-3} \][/tex]
Simplifying this, we obtain:
[tex]\[ x = -12 \][/tex]
So, the solution to the equation is [tex]\(-12\)[/tex].
### Step 4: Verify with Given Options
We are given the options:
- [tex]\( x = -15 \)[/tex]
- [tex]\( x = -12 \)[/tex]
- [tex]\( x = 12 \)[/tex]
- [tex]\( x = 15 \)[/tex]
From our calculated result, the correct value of [tex]\( x \)[/tex] is [tex]\(-12\)[/tex].
Thus, the solution to the equation [tex]\(-10x + 1 + 7x = 37\)[/tex] is:
[tex]\[ \boxed{-12} \][/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.